Diversity performance of body communication channels using switching parasitic disk-loaded monopole array antenna - Kamarudin, M. R. (Wiley-Blackwell, 2009)
In the cellular systems diversity reception techniques such as space, time, frequency, polarization, and pattern diversity are widely used to minimize or mitigate the effect of multipath fading due to scattering, diffraction, and reflection of the transmitted signal. Practically, these methods can be applied either at the base station or at the mobile terminal. In the on-body environment, fading has also been found to be significance. Space diversity has been useful in such channels. In this article, a switching parasitic disk-loaded monopole array antenna (also called pattern diversity antenna) was used to investigate diversity performance in on-body channels. There were five body channels that have been investigated that are belt-to-chest, belt-to-wrist, belt-to-ankle, belt-to-head, and belt-to-back channels. The diversity data was analyzed using a switched diversity combining method. Diversity gain has been measured at outage of 1% and 10% for five on-body channels. The results show significance gains are achieved for nonline-of-sight channels especially the ankle and wrist channels which have involved lots of antenna movement. In contrast, very little gain is obtained for line-of-sight channel particularly for the chest channel as only one beam was used for most of the time.